The complete chloroplast genome sequence of Limonium sinense (Plumbaginaceae) - Li, Jianfang (Mitochondrial DNA B Resour, 2020)
Limonium is a species-rich genus in Plumbaginaceae. In this study, we determined the complete chloroplast genome of Limonium sinense for potential phylogenomic analysis in the future. The plastome is 174,033 bp in length, with a large single-copy region (LSC) of 96,128 bp, a small single-copy region (SSC) of 13,517 bp and a pair of inverted repeat regions (IRs) of 32,194 bp. It contains 132 genes, including 84 protein-coding genes, 37 tRNA genes, 8 rRNA genes, and 3 pseudogenes. The overall GC content is 36.7%, while the corresponding values for the LSC, SSC, and IR region are 34.9, 31.1, and 40.6%, respectively. The phylogenetic analysis supported that L. sinense was clustered together with Plumbago auriculata in family Plumbaginaceae.